Stunting Risk Factors For Children Aged 6 - 36 Months in The Region of Sambirejo Health Center, Langkat, North Sumatera - Harahap, Juliandi; Amelia, Rina; Andayani, Lita Sri; Lubis, Nenni Dwi Aprianti; Aulia, Destanul (Rifa'Institute, 2022)
Introduction: Stunting is a chronic malnutrition condition caused by a numeuros of factors, including inadequate maternal nutritional nutrition during pregnancy, inadequate exclusive breastfeeding, and infectious diseases. There are also some indirect factors .Objective: The objective of this study was to investigate the risk factors for stunting in children aged 6-36 months in the Sambirejo Health Center area. study. Method: This study is an observational analytic study using a cross-sectional approach that gathers data via a questionnaire. Sampling Techniques using the Non- Probability Sampling technique, and the sample size was estimated using the Lemeshow formula. The Prevalence Ratio (PR) was calculated to evaluate the strength of the link between the factors assumed to be linked with stunting. Result and Discussion: Of the 65 samples, Four children were stunted, while 61 were not. Infants who were not exclusively breastfed, infants with a history of LBW, infants with a history of SBL, and family planning of 2 years both were risk factors for stunting in this study. Conclusions: Some variables in this study had no impact on the incidence of stunting. In this study, the risk factors for stunting were LBW, SBL, and infants without exclusive breastfeeding, and child spacing was a neutral factor for the occurrence of stunting in children aged 6-36 months.